UNEMPLOYMENT CURRICULUM OUTCOMES, PSYCHO-SOCIAL CHARACTERISTICS AND ENTREPRENEURIAL ABILITIES OF THEOLOGICAL SEMINARY GRADUATES - Abam Arikpo; Aquah Patricia A. (European Scientific Journal, ESJ, 2014)
The purpose of this study was to ascertain the relationship of curriculum outcomes, personality trait, gender role stereotype, and common small scale business practices to entrepreneurial abilities of theological seminary graduates. Forty five (45) theological seminary graduates in the denominations of the unemployed, the self employed, the private sector employed and government employed were purposively drawn for the study. Three research questions guided the study. Five questionnaires were used in data collection. The data were analysed using Multiple Regression. The result indicated that of the independent variables considered only the effect of cognitive curriculum outcomes was significant on the entrepreneurial abilities of theologies seminary graduates (p<0.05).